Transformation behavior in NiTi-20Ta and NiTi-20Nb SMAs - Dagdelen, Fethi; Aydogdu, Y. (Springer, 2019)
Shape memory alloys Ni30Ti50X20 (at.% X = Nb, niobium, and Ta, tantalum) were produced through arc-melting method. Phase transformation temperatures were studied by using differential scanning calorimetry (DSC), and microstructures were examined with the aid of optical microscopy, scanning electron microscopy-energy dispersive X-ray (SEM-EDX) and X-ray diffraction (XRD). According to DSC results obtained at heating rate of 10 C min(-1), transformation temperature of Ni Ni30Ti50Nb20 alloy was determined as A(s) = 24.8 degrees C, A(f) = 62.1 degrees C, M-s = 27.9 degrees C, M-f = - 10.7 degrees C and that of Ni30-Ti50Ta20 alloy was determined as A(s) = 84.0 degrees C, A(f) = 110.4 degrees C, M-s = 56.0 degrees C, M-f = 32.1 degrees C. These results have shown that NiTi alloys which were added Nb and Ta at the rate of 20% demonstrate shape memory properties. Also, it has been identified that Ni30Ti50Ta20 and Ni30Ti50Nb20 alloys demonstrate B19(iota) <--> H B2 phase transformation. Thermal activation energy calculated by Kissinger method was found: E-a = 114.208 kJ mol(-1) for NiTiNb and E-a = 105.819 kJ mol(-1) for NiTiTa. It was observed that as a result of SEM-EDX analysis, there exist Nb 2 Ti phase (Nb rich) in NiTiNb alloy and Ta 2 Ti phase (Ta rich) in NiTiTa alloy. These phases were supported with XRD results. In micro-hardness measurements, it was determined that NiTiNb shape memory alloy has the value of 361HV(0.1) micro-hardness and NiTiTa shape memory alloy has the value of 420 HV0.1 micro-hardness.
Keywords: Shape memory alloy; Martensite phase; Microstructure